Fibrinolysis in Decidual Spiral Arteries in Late Pregnancy - Sheppard, B L; Bonnar, J (Thrombosis and Haemostasis, 1978)
The fibrinolytic activity of the intimal cells of decidual spiral arteries and the syncytium of placental villi was studied by electron microscopy in ten normal full-term human pregnancies using a modification of the fibrin slide technique. Endothelial cells lining the intima of the decidual spiral arteries showed a considerably greater fibrinolytic activity than intimal cytotrophoblast and the syncytiotrophoblast showed no activity.The replacement of endothelial cells by an intimal lining of cytotrophoblast, and the presence of cytotrophoblast in the media, appears to play an important role in the reduction of the fibrinolytic activity of the vessel. This inhibition of fibrinolytic activity in the utero-placental arteries may be the physiological mechanism which controls fibrin deposition in these vessels and on the placental villi.